Phytotoxicity, uptake, and translocation of two halogenated flame retardants and cadmium in two rice varieties - Liu, Ruiyuan; Xie, Hui; Xu, Yuxin; Sun, Fengxia (Frontiers in Environmental Science, 2022)
Dechlorane Plus (DP) and Tetrabromobisphenol A (TBBPA) are the halogenated flame retardant with the highest production volume, cadmium (Cd) is regarded as one of the hazardous heavy metals due to its bio toxicity and bioaccumulation in the environment, and it will cause environmental pollution and affect human health, so a pot experiment was conducted to investigate the phytotoxicity on seed germination and seedling of two rice varieties. The results showed that with the increasing of DP, TBBPA and Cd concentrations in soil, the germination rate, germination index and vigor index of two rice varieties decreased, and the germination of Number 7 rice was affected more than Number 1 rice. Halogenated flame retardants and Cd in soil significantly promoted root activity and proline, and significantly inhibited protein and soluble sugar contents of two rice varieties. In addition, the responses of the two rice varieties seedlings to different pollutants were obviously different. The activity of superoxide dismutase (SOD) in two kinds of rice was improved, and a large amount of malonyldialdehyde (MDA) was induced. But the activity of catalase (CAT) in Number 7 rice was increased under the action of DP and TBBPA, while the activity of Number 1 rice was increased under the action of DP and inhibited under the pollution of TBBPA. Bioaccumulation factors of DP and Cd were 0.025-0.042 and 6.59-14.20, bio transport coefficients were 0.39-0.48 and 0.034-0.087. There was no significant difference in the bioaccumulation of DP in the two rice varieties, but TBBPA and Cd were more easily bio accumulated in the Number 1 rice. These findings would provide some essential information for interpreting the ecological risks of two halogenated flame-retardants and Cd in plants.